Hemoperitoneum: a diagnostic dilemma. A solid ovarian tumour mimicking ruptured ectopic pregnancy - Sheelaa, Wills G.; Manivasakan, Jayasree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
39 year old sterilized women presented like ruptured ectopic pregnancy with 40 days amenorrhea, pain, and shock Urine Pregnancy Test negative. Culdocentesis was positive. Ultra sonogram confirmed hemoperitoneum and TO mass. Laparotomy revealed left solid ovarian tumour with tumour mass protruding from perforated site and hemoperitoneum. Histological diagnosis was granulosa cell (GC) tumour Stage 1c.